2010
DOI: 10.4152/pea.201003203
|View full text |Cite
|
Sign up to set email alerts
|

Use of Experimental Designs to Evaluate the Influence of 2-Mercaptobenzimidazole on the Corrosion of Mild Steel in HCl (1 M) Environment in the Presence of Alcohol Ethoxylate

Abstract: The present study attempted to investigate the best conditions for the use of a mixture of 2-mercaptobenzimidazole and alcohol ethoxylate (C13) as corrosion inhibitor of mild steel in 1 M HCl through the use of the surface response methodology. A matrix of Doelhert to 4 factors was used as the experimental design in this research as it permits the use of the response surface methodology in a spherical field. The response used in the exploitation of the design was the determination of the inhibitor efficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Most of the well known inhibitors are organic compounds containing nitrogen [7][8][9][10][11][12][13], oxygen [9,[11][12][13] or nitrogen and sulfur [14,16] in their functional groups. Some studies have shown that the inhibition of the corrosion process is mainly decided by the formation of donor-acceptor surface complexes between free or π electrons of an inhibitor and vacant d orbital of a metal [17][18][19]. The aim of this work is to evaluate and to compare the corrosion inhibition efficiency of some phenyltetrazole substituted compounds for mild steel in 1 M HCl at 25 °C using weight loss measurement, potentiodynamic polarization and electrochemical impedance spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the well known inhibitors are organic compounds containing nitrogen [7][8][9][10][11][12][13], oxygen [9,[11][12][13] or nitrogen and sulfur [14,16] in their functional groups. Some studies have shown that the inhibition of the corrosion process is mainly decided by the formation of donor-acceptor surface complexes between free or π electrons of an inhibitor and vacant d orbital of a metal [17][18][19]. The aim of this work is to evaluate and to compare the corrosion inhibition efficiency of some phenyltetrazole substituted compounds for mild steel in 1 M HCl at 25 °C using weight loss measurement, potentiodynamic polarization and electrochemical impedance spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…The best pretreatment conditions were determined which caused a protective Cu‐AMT film on the bronze surface. Experimental designs were also used for optimizing coatings deposition at various substrates . The Plackett–Burman experimental design was used by Khanmohammadi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental designs were also used for optimizing coatings deposition at various substrates. [17][18][19][20][21][22][23][24][25][26][27] The Plackett-Burman experimental design was used by Khanmohammadi et al [28] to optimize the synthesis of polyaniline TiO (PANI-TiO) composite for carbon steel preservation. The authors applied a screening factorial design to identify the most significant variable on the PANI-TiO composite preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The Gerischer impedance was introduced to describe a diffusion type impedance in which the species also participates in a chemical reaction along the diffusion path [18]. This impedance was generally observed in a mixed conducting solid electrolyte systems [2].…”
Section: A Chaabani Et Almentioning
confidence: 99%
“…Nowadays, the chemometric approach is considered as powerful tool for studying the corrosion and protection process. Many works introduced the use of experimental designs for understand metals corrosion and inhibition [12]- [18]. Among them, only de Lago et al [19] used the experimental design to study the effect of 2-amino-5-mercapto-1,3,4-thiadiazole (AMT) as inhibitor for bronze protection in artificial rainwater.…”
Section: Introductionmentioning
confidence: 99%